KONTROVERSI PERSYARATAN PENDIDIKAN CALON ANGGOTA LEGISLATIF PADA PASAL 240 UNDANG-UNDANG NOMOR 7 TAHUN 2017 PRESPEKTIF FIQIH SIYASAH DUSTURIYYAH - Ulfa Astin; Saadatul Maghfira; Zainuddin Zainuddin; Khairina Khairina (UIN Mahmud Yunus Batusangkar, 2022)
This study examines the Educational Requirements for Legislative Member Candidates in Law Number 7 of 2017 from Fiqh Siyasah Dusturiyah Perspective. From this problem, the question arises: How is the conversion that has occurred to the educational requirements for legislative candidates according to Law Number 7 of 2017, and whether legislative candidates with high school graduates said to be experts to become people's representatives? The type of research used is library research using qualitative research methods, with descriptive analysis. The requirements for high school graduate legislative candidates in article 240 letter (e) of Law Number 7 of 2017 concerning Elections, that from members of the public, political observers, to legislative members themselves, there are pros and cons with the education requirements of legislative candidates who only graduate from high school which can be said to be not yet an expert or knowledgeable with limited education and the age of 21 is classified as a very young age and minimal experience